Carbohydrate-based approach for the total synthesis of 1,3-polyol/alpha-pyrone antifungal natural products - Ramana, Chepuri V.; Srinivas, B.; Puranik, Vedavati G.; Gurjar, M. K. (Journal of Organic Chemistry, 2005)
An elimination and stereoselective hydrogenation of alpha-D-glucoheptonic-gamma-lactone derivative has been applied to prepare a differentially protected anti,anti-1,3,5-triol system, the utility of which has been extended for the total synthesis of anti-fungal 1,3-polyol/alpha-pyrone natural products.

Carbohydrate-based approach for the total synthesis of strictifolione - Ramana, C. V.; Raghupathi, N.; Gurjar, M. K.; Chorghade, Mukund S. (Tetrahedron Letters, 2005)
A chiral pool approach starting with D-glucose, using the Yamaguchi protocol and a Z-selective HWE reaction followed by lactonization, has been applied to execute the total synthesis of strictifolione. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: D-Glucose; double elimination; Horner-Wadsworth-Emmons reaction; lactonization; strictifolione; Yamaguchi protocol

Convenient synthesis of the enantiomerically pure beta-blocker (S)-betaxolol using hydrolytic kinetic resolution - Joshi, Ramesh A.; Garud, Dinesh R.; Muthukrishnan, Murugan; Joshi, Rohini R.; Gurjar, M. K. (Tetrahedron-Asymmetry, 2005)
Enantiopure (S)-betaxolol was prepared in an extremely simple and practical way using hydrolytic kinetic resolution of a terminal epoxide by Jacobsen's catalyst. High enantiomeric purity (99% ee) has been achieved and the method is amenable to industrial scale-up. (c) 2005 Elsevier Ltd. All rights reserved.

Ring-closing metathesis mediated total synthesis of microcarpalide and herbarumin III - Gurjar, M. K.; Nagaprasad, R.; Ramana, C. V.; Karmakar, S.; Mohapatra, Debendra K. (Arkivoc, 2005)
Total synthesis of naturally occurring microcarpalide and herbarumin III are described. The ring-closing metathesis (RCM) approach to coin the medium sized rings present in their molecular structures form the basic premise of this investigation.
Keywords: herbarumin III; microcarpalide; microfilament; phosphodiesterase; ring-closing metathesis (RCM)

Simple and practical approach to enantiomerically pure (S)-3-hydroxy-gamma-butyrolactone: synthesis of (R)-4-cyano-3-hydroxybutyric acid ethyl ester - Kumar, P.; Deshmukh, A. N.; Upadhyay, R. K.; Gurjar, M. K. (Tetrahedron-Symmetry, 2005)
The oxidation of alpha- or beta-(1,4) linked disaccharides or oligosaccharides with cumene hydroperoxide in the presence of a base gave (S)-3,4-dihydroxybutyic acid, which was cyclized under acidic conditions to furnish (S)-3-hydroxy-gamma-butyrolactone. This was subsequently converted into (R)-cyano-3-hydroxybutyric acid ethyl ester, an intermediate for statin based drugs and other related compounds. (c) 2005 Elsevier Ltd. All rights reserved.

Stereoselective syntheses of (+)-proto, (-)-gala quercitols and carba-L-rhamnose from D-(-)-quinic acid - Murugan, A. Vadivel; Yadav, A. K.; Gurjar, M. K. (Tetrahedron Letters, 2005)
Efficient syntheses of (+)-proto, (-)-gala quercitols and carba-L-rhamnose front D-(-)-quinic acid are described. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: (+)-proto quercitol; (-)-gala quercitol; carba-L-rhamnose; cyclohexanepentols; D-(-)-quinic acid; stereoselectivity

Stereoselective synthesis of (2S,7S)-7-(4-phenoxymethyl)2-(1-N-hydroxyureidyl-3-butyn-4-yl)oxepane: a potential anti-asthmatic drug candidate - Gurjar, M. K.; Rao, B. V.; Krishna, L. M.; Chorghade, Mukund S.; Ley, S. V. (Tetrahedron-Asymmetry, 2005)
We have achieved a short, efficient stereoselective synthesis of 7-membered oxepane derivatives with potential against asthma. Highlights of our synthetic strategy are regioselective oxidation of a hydroxyl group and efficient ring closure of an open chain aldehyde to a 2-benzenesulfonyl oxepane derivative with PhSO2H. Surprisingly the cis-isomer showed better activity than the traps-isomer. (C) 2005 Elsevier Ltd. All rights reserved.

Stereoselective synthesis of spiroannulated cyclopentenones by the Pauson-Khand reaction on carbohydrate derived enynes - Hotha, Srinivas; Maurya, S. K.; Gurjar, M. K. (Tetrahedron Letters, 2005)
The stereoselective synthesis of spiroannulated cyclopentenones by the Pauson-Khand reactions on hexose and pentose derived enynes was achieved under carbon monoxide free conditions using a stoichiometric quantity of Co-2(CO)(8). The cobalt complex of the alkyne was cleaved using dimethoxyethane-acetonitrile at 85 degrees C to furnish spiroarmulated cyclopentenones in 75-94% yields. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: carbohydrates; cyclopentenone; diversity oriented synthesis; Pauson-Khand reaction

Vapor phase oxidation of 4-fluorotoluene over vanadia-titania catalyst - Maurya, S. K.; Patil, P.; Shubhangi B. Umbarkar; Gurjar, M. K.; Dongare, Mohan K.; Rudiger, S.; Kemnitz, E. (Journal of Molecular Catalysis A - Chemical, 2005)
The vapor phase oxidation of 4-fluorotoluene has been carried out over vanadia-titania catalysts with moderate conversion and selectivity for 4-fluorobenzaldehyde. Two series of V2O5/TiO2 catalysts with 1-10 mol% vanadia were prepared by sol-gel technique using vanadium and titanium peroxide as vanadia and titania precursors respectively and by impregnation technique using vanadium peroxide on anatase titania support. The samples were characterized by X-ray diffraction, NH3-TPD, FT-IR and BET surface area measurements. The XRD of the catalysts prepared by impregnation technique showed retention of the anatase titania whereas the catalysts prepared by sol-gel technique showed the formation of rutile titania with minor amount of anatase phase at lower vanadia content (1-3 %), which completely transformed into anatase phase at higher vanadia loading. The samples prepared by sol-gel method showed higher acidity and surface area compared to the samples prepared by impregnation. Pyridine adsorption study by FT-IR revealed the presence of Lewis acidity at lower vanadia loading (1-3 %) and presence of both Lewis as well as Bronsted acidity at higher vanadia loading. The catalytic activity for oxidation of 4-fluorotoluene increased with vanadia loading in the sol-gel catalysts. The catalysts prepared by impregnation technique were found to be less active. However the selectivity for 4-fluorobenzaldehyde decreased with increase in vanadia content. The influence of vanadia loading, reaction temperature and contact time on the catalytic activity for 4-fluorotoluene oxidation has been investigated. The structure of the catalyst and its catalytic activity has been correlated. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Catalyst; fluorotoluene; Oxidation; vanadia-titania; vapor phase

Convenient chemoenzymatic synthesis of (1S,7aS)-1-hydroxy-5-oxo-4-(2 `-carboxyethyl)-7a-methyltetrahydro-indane - a key intermediate of steroids - Kalkote, Uttam R.; Purude, A. N.; Puranik, Vedavati G.; Gurjar, M. K. (Journal of Molecular Catalysis B-Enzymatic, 2006)
A porcine pancreatic lipase mediated enzymatic hydrolysis of (+/-)-1-acetoxy-5-oxo-4-(2 `-carbomethoxyethyl)-7a-methyltetrahydroindane (5b) furnished (1S,7aS)-1-acetoxy-5-oxo-4-(2 `-carbomethoxyethyl)-7a-methyltetrahydro-indane (9) and (1R,7aR)-1-hydroxy-5-oxo-4-(2 `-carbomethoxyethyl)-7a-methyltetrahydro-indane (8) with > 99% e.e. which on further chemical hydrolysis gave 1 and ent-1, key intermediates of steroids. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: chemoenzymatic method; Enzymatic hydrolysis; steroids; terpenoids